The Public Opinion In The Modern History Of Political Thought According To Jurgen Habermas - Hamzaj, Enkelejda (European Scientific Journal, ESJ, 2016)
Is not easy to make in a few lines a presentation of Habermas’s thinking regarding to public opinion in the history of political thought. One of the most interesting sections of all habermasian discussion â€“ developed not only in his opera History and critiques of public opinion but in others too â€“ lies in clarifying how the public opinion concept was evaluate by philosophers of different political orientations during the modern era. According to Habermas, to do this analysis should go under the tracks of Hobbes, Rousseau, Kant and Hegel. Some of these authors appreciate and value the role of the public opinion while others do not believe in its function. It is not a coincidence that the"classic" treatment of the public opinion concept culminates with Kant, the author, who is considered one of the greatest luminaries in Europe. While we find in Hegel a devaluation of the public opinion, compared with the science, and this depreciation is parallel to the depreciation of the civil society against the State. On the other side we will see other contemporary authors analysis regarding public opinion, like Nicola Matteuci and Giuseppe Bedeschi and their thoughts compared with Habermas thoughts. To understand the function of public opinion I will show its specific characteristics throughout history from the Greek polis up to the French Revolution and the creation of the bourgeoisie class.